2020
DOI: 10.3892/ol.2020.11687
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑126 exerts antitumor functions in ovarian cancer by targeting EGFL7 and affecting epithelial‑to‑mesenchymal transition and ERK/MAPK signaling pathway

Abstract: Ovarian cancer (OC) is a common gynecological malignant carcinoma worldwide. Accumulating research has revealed that multiple microRNAs (miRNAs) are abnormally expressed at different levels in various malignancies, playing vital roles in tumorigenesis. This study investigated the regulatory functions and potential mechanism of miR-126 in OC proliferation, invasion and migration. It was found that miR-126 was prominently downregulated in OC. Moreover, the decrease of miR-126 promoted the aggressive phenotypes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…These results agree with previously reported data, where it was shown that the frequency of BRCA1 methylation in WBCs was higher in patients with OC than in controls and that it was associated with risk for HGSOC (22). miR-126 is downregulated in tumor tissues compared with that in normal adjacent tissues in several cancer types, including BC, OC and colorectal cancer, and this decrease is associated with higher malignancy tumor grade and metastasis (31,32,38). The restoration of miR-126 has been demonstrated to inhibit metastasis properties in these cancer types (32,38).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results agree with previously reported data, where it was shown that the frequency of BRCA1 methylation in WBCs was higher in patients with OC than in controls and that it was associated with risk for HGSOC (22). miR-126 is downregulated in tumor tissues compared with that in normal adjacent tissues in several cancer types, including BC, OC and colorectal cancer, and this decrease is associated with higher malignancy tumor grade and metastasis (31,32,38). The restoration of miR-126 has been demonstrated to inhibit metastasis properties in these cancer types (32,38).…”
Section: Discussionsupporting
confidence: 92%
“…miR-126 is downregulated in tumor tissues compared with that in normal adjacent tissues in several cancer types, including BC, OC and colorectal cancer, and this decrease is associated with higher malignancy tumor grade and metastasis (31,32,38). The restoration of miR-126 has been demonstrated to inhibit metastasis properties in these cancer types (32,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, F1012-2 induced DNA damage response via targeting the MAPK pathway in breast cancer [24]. Another study showed that EGFL7 regulated the growth of breast cancer cells via the MAPK pathway [25]. These studies, together with our findings, confirmed that the MAPK pathway could serve as a promising target of breast cancer.…”
Section: Discussionsupporting
confidence: 81%
“…We previously demonstrated that miR-126 acts as a tumor suppressor via the down-regulation of CXCR4 and the inhibition of the RhoA/ROCK pathway in colon cancer [9]. Other researchers reported that miR-126 exerts antitumor functions in various types of cancers, such as ovarian cancer, liver cancer, gastric cancer, and non-small cell lung cancer [10,11]. MiR-126 is also involved in the regulation of in ammatory events [12].…”
mentioning
confidence: 99%